Attentional Biases fixed or dynamic : a study on the incongruency hypothesis and the correspondence principle - Tan, Yu Jia (2016)
Two types of attentional biases have been found to be inherent in humans: the more common negativity bias and a positivity bias (Matlin& Slang, 1978; Skowronski & Carlston, 1987; Rozin & Royzman, 2001). Contradictory information about which bias is dominant has led to the study of a possible single mechanism linking the two biases. Rothermund (2008) posited that the biases might be the result of a counter regulation mechanism when humans are given an outcome focus. A negativity bias arises when the outcome focus is positive and vice versa. However, given that humans are driven to maintain or enhance a positive well-being, it was speculated in this study that the attentional biases of participants should abide by both a counter regulation and a correspondence mechanism if they are given a positive outcome focus. Similarly, they were expected to follow only the counter regulation principle if they were given a negative outcome focus. The present study thus hopes to see which mechanism is more accurate and to confirm a negativity bias in the absence of any outcome focus. A modified version of the flanker task by Rothermund was used and participants were randomly induced with a negative, positive or neutral outcome foci. The participants were told to identify happy, sad or neutral faces while ignoring distractor faces and results supported the existence of a counter regulation mechanism in both attentional bias under an outcome focus. The contribution of this study to the scarce literature regarding counter regulation and what it means for clinical therapy were also discussed.